Fatty liver mediates the association of hyperuricemia with prediabetes and diabetes: a weighting-based mediation analysis - Basnet, Til Bahadur; Du, Shanshan; Feng, Ruimei; Gao, Jie; Gong, Jiamin; Ye, Weimin (Frontiers in Endocrinology, 2023)
Background: The present study evaluated the role of multiple mediators, namely fatty liver, body mass index (BMI), and dyslipidemia, in the association between hyperuricemia and diabetes status. Methods: Baseline data from the ongoing Fuqing cohort (5336 participants) were analyzed to investigate the association of hyperuricemia with diabetes status using a multinomial logistic regression model. Furthermore, causal mediation analysis with the weighting-based approach was performed to estimate hyperuricemia's total natural direct (tnde) and total natural indirect effect (tnie) on prediabetes and diabetes risk, mediating jointly via fatty liver, BMI, and dyslipidemia. Results: In multinomial analysis without considering mediators’ effects, hyperuricemia was associated with a higher risk of prediabetes only (odds ratio: 1.25; 95%CI: 1.09 - 1.43; P < 0.001). When the fatty liver, BMI, and dyslipidemia were considered as multiple mediators in the association, hyperuricemia was linked with both prediabetes (tnde: 1.11; 95%CI: 1.04 - 1.11, tnie: 1.07; 95%CI: 1.05 - 1.09 and overall proportion mediated (pm): 42%; 95%CI: 27 - 73%) and diabetes risk (tnde: 0.96; 95%CI: 0.82 - 1.14, tnie: 1.25; 95%CI: 1.18 - 1.33 and pm: 100%; 95%CI: 57 - 361%). Hyperuricemia showed significant tnde, te, and tnie, mediated by fatty liver jointly with dyslipidemia (pm = 17%) or BMI (pm = 35%), on prediabetes risk indicating fatty liver had a robust mediating effect in the association. Conclusions: Hyperuricemia could increase prediabetes or diabetes risk, partially mediating via fatty liver, BMI, and dyslipidemia. Fatty liver is the crucial mediator in the association between hyperuricemia and prediabetes or diabetes. Keywords: Hyperuricemia; Prediabetes; Diabetes; Multiple mediators; Fatty liver; Fuqing cohort; China